Very High Cycle Fatigue Crack Initiation Mechanism in Nugget Zone of AA 7075 Friction Stir Welded Joint - Chao He; Kazuhiro Kitamura; Kun Yang; Yong-jie Liu; Qing-yuan Wang; Qiang Chen (Advances in Materials Science and Engineering)
Very high cycle fatigue behavior of nugget zone in AA 7075 friction stir welded joint was experimentally investigated using ultrasonic fatigue testing system (20 kHz) to clarify the crack initiation mechanism. It was found that the fatigue strength of nugget zone decreased continuously even beyond 107 cycles with no traditional fatigue limits. Fatigue cracks initiated from the welding defects located at the bottom side of the friction stir weld. Moreover, a special semicircular zone could be characterized around the crack initiation site, of which the stress intensity factor approximately equaled the threshold of fatigue crack propagation rate. Finally, a simplified model was proposed to estimate the fatigue life by correlating the welding defect size and applied stress. The predicted results are in good agreement with the experimental results.